Therapeutic effects of physostigmine during systemic inflammation - Effenberger-Neidnicht K; Jägers J; Verhaegh R; Kirsch M (Dove Medical Press, 2018)
Katharina Effenberger-Neidnicht,1 Johannes Jägers,2 Rabea Verhaegh,1 Michael Kirsch1 1Institute of Physiological Chemistry, University Hospital Essen, Essen, Germany; 2Institute of Physiology, University Hospital Essen, Essen, Germany Introduction: Usually, physostigmine is used as antidote for anticholinergic poisons in order to improve hemodynamics and cardiac output. In addition, it causes beneficial effects during sepsis when added timely. Here, we studied whether physostigmine improves hemodynamics when treatment during systemic inflammation was delayed. Methods: Two series of randomized studies with overall 44 rats were conducted. Systemic inflammation was induced by lipopolysaccharide (LPS) infusion (0.5 mg LPS/kg×h). Physostigmine (PHY) was intravenously applied after an LPS infusion period of 90 minutes (50 µg PHY/kg within 10 minutes) with (series 1) and without (series 2) additional volume loading. Hemodynamic parameters, blood gases, and parameters for tissue damage were periodically determined for up to 180 minutes. Results: Even though volume was additionally administered (series 1), LPS caused a reduction of peripheral blood flow. Treatment with PHY improved hemodynamics in macrocirculation (mean arterial blood pressure) and microcirculation (peripheral blood flow). PHY neither affected alterations in blood gases, electrolyte homeostasis, and glucose metabolism nor prevented intestinal damage induced by LPS. In series 2, without any additional volume loading, PHY likewise resulted in an improvement of the LPS-induced alterations in macro- and microcirculation, but finally worsened the LPS-mediated effects on plasma parameters for tissue damage such as creatine kinase, probably due to the lack of volume and a further damage to the heart. Conclusion: The present results demonstrated that hemodynamic responses to PHY may not only be visible in patients with anticholinergic drug overdose but also be visible in septic patients, provided that fluid intake of these patients is adequate. Keywords: sepsis, septic shock, lipopolysaccharide, peripheral blood flow, mean arterial blood pressure, volume load, serine, rat